2018
DOI: 10.3389/fphys.2018.01358
|View full text |Cite
|
Sign up to set email alerts
|

Invalidation of Microsomal Prostaglandin E Synthase-1 (mPGES-1) Reduces Diet-Induced Low-Grade Inflammation and Adiposity

Abstract: Chronic low-grade inflammation is known to be linked to obesity, and to occur in the early stages of the disease. This mechanism is complex and involves numerous organs, cells, and cytokines. In this context, inflammation of white adipose tissue seems to play a key role in the development of obesity. Because of its properties, prostaglandin E2 (PGE2), an emblematic inflammatory mediator, has been proposed as an actor linking inflammation and obesity. Indeed, PGE2 is involved in mechanisms that are dysregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(79 reference statements)
5
7
0
Order By: Relevance
“…ARDS, and thereby prevent ICU admissions and decrease mortality, is based on the role PGE2 has as an inflammatory modulator in viral infections and further literature supporting that targeted PGE2 inhibition enhances antiviral immunity (Ricciotti and Fitzgerald, 2011;Coulombe et al, 2014;Bergqvist et al, 2020) (Figure 2). That PGE2 belongs to the many factors contributing to the uncontrolled inflammation observed in obese individuals adds to our hypothesis (González-Périz and Clària, 2010; Pierre et al, 2018). Besides, mPGES-1 knock-out mice have been shown to reduce diet-induced lowgrade inflammation and adiposity (Pierre et al, 2018).…”
Section: Selective Mpges-1 Inhibition To Attenuate Covid-19 Associatesupporting
confidence: 62%
See 1 more Smart Citation
“…ARDS, and thereby prevent ICU admissions and decrease mortality, is based on the role PGE2 has as an inflammatory modulator in viral infections and further literature supporting that targeted PGE2 inhibition enhances antiviral immunity (Ricciotti and Fitzgerald, 2011;Coulombe et al, 2014;Bergqvist et al, 2020) (Figure 2). That PGE2 belongs to the many factors contributing to the uncontrolled inflammation observed in obese individuals adds to our hypothesis (González-Périz and Clària, 2010; Pierre et al, 2018). Besides, mPGES-1 knock-out mice have been shown to reduce diet-induced lowgrade inflammation and adiposity (Pierre et al, 2018).…”
Section: Selective Mpges-1 Inhibition To Attenuate Covid-19 Associatesupporting
confidence: 62%
“…That PGE2 belongs to the many factors contributing to the uncontrolled inflammation observed in obese individuals adds to our hypothesis (González-Périz and Clària, 2010; Pierre et al, 2018). Besides, mPGES-1 knock-out mice have been shown to reduce diet-induced lowgrade inflammation and adiposity (Pierre et al, 2018).…”
Section: Selective Mpges-1 Inhibition To Attenuate Covid-19 Associatesupporting
confidence: 62%
“…Furthermore, microsomal PGE synthase-1 (mPGES-1) is an enzyme that specifically catalyzes the final step of PGE 2 biosynthesis. The mPGES-1 knockout mice fed a HFD had lower body weight gain and reduced adiposity, which were accompanied by a decrease in adipose tissue inflammation compared to the inflammation of littermate control mice [31]. In addition, the upregulation of adipocyte COX-2, PGE 2 , and EP3 signaling, during obesity-associated adipocyte hypertrophy and hypoxia, was causally linked to the augmented gene expression and protein production of inflammatory adipokines.…”
Section: Cox-2-derived Pgs and Obesity Associated Complicationsmentioning
confidence: 99%
“…The results of a retrospective cohort study that recruited 402 PD patients demonstrated that the serum C-reactive protein level is an independent predictor of technique failure (34), suggesting that systemic inflammation is associated with technique survival. mPGES-1/PGE2 plays a critical role in the progression of multiple diseases via proinflammatory mechanisms (28,35,36). We explored the effect between mPGES-1/PGE2 signaling and the NLRP3 inflammasome in high-glucose-stimulated RPMCs.…”
Section: Discussionmentioning
confidence: 99%